Content Optimization of Polyphenylene Sulfide Composites Filled with Carbon Fibers of Different Size; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Grishaeva N. Yu.; Bochkareva S. A.; Panin S. V. Sergey Viktorovich; Le Thi My Hiep; Lyukshin B. A.; Panov I. L.; Nguyen Dyk An (2019, 2019)
Title screen